2014
DOI: 10.1016/j.soilbio.2014.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the molecular structure and mean residence time of occluded organics in a lithosequence of soils under ponderosa pine

Abstract: Occluded, or intra-aggregate, soil organic matter (SOM) comprises a significant portion of the total C pool in forest soils and often has very long mean residence times (MRTs). However, occluded C characteristics vary widely among soils and the genesis and composition of the occluded organic matter pool are not well understood. This work sought to define the major controls on the composition and MRT of occluded SOM in western U.S. conifer forest soils with specific focus on the influence of soil mineral assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…These data suggest that parent material composition is not a driving factor regulating carbon sequestration in this lithosequence. This is in agreement with the findings of Heckman et al (2014), who found no significant differences in soil organic carbon or occluded soil organic matter attributable to variations in lithology, concluding that climate, fire frequency and preferential occlusion of charcoal are more substantial factors in carbon dynamics than initial parent material composition.…”
Section: Soil Physiochemical Propertiessupporting
confidence: 92%
“…These data suggest that parent material composition is not a driving factor regulating carbon sequestration in this lithosequence. This is in agreement with the findings of Heckman et al (2014), who found no significant differences in soil organic carbon or occluded soil organic matter attributable to variations in lithology, concluding that climate, fire frequency and preferential occlusion of charcoal are more substantial factors in carbon dynamics than initial parent material composition.…”
Section: Soil Physiochemical Propertiessupporting
confidence: 92%
“…Surface area was measured under N 2 and modeled using the BET equation [37]. Soils were density separated into free/light (F/L), occluded (OCC) and heavy fractions (HF) using a sodium polytungstate (SPT) solution adjusted to a density of 1.8 g cm −3 [33,38]. In brief, soils were mixed with SPT and centrifuged to separate low density organics (F/L) from the rest of the soil.…”
Section: Methodsmentioning
confidence: 99%
“…Soil is the major C pool in terrestrial ecosystems and has a longer turnover time than vegetation (Schmidt et al., ). A central topic in previous studies on soil organic C (SOC) dynamics is SOC turnover time (τ soil ) and its determinants (Heckman et al., ; Koven et al., ; Schimel et al., ). It has been documented that at a small spatial scale, soil C turnover is mainly dependent on soil temperature and moisture (Craine, Fierer, & McLauchlan, ; Davidson & Janssens, ; Thomsen, Schjønning, Jensen, Kirstensen, & Christensen, ), soil chemical properties (Schindlbacher et al., ; Xu, He, & Yu, ; Xu, Shi, et al., ), C quality (Chen, Liang, et al., ) or soil microbial community (Chen, Li, Lan, Hu, & Bai, ; Cleveland, Nemergut, Schmidt, & Townsend, ), while at national and global scales, latitude, altitude and associated climatic variables are suggested to be responsible for the variability of τ soil (Chen, Huang, Zou, & Shi, ).…”
Section: Introductionmentioning
confidence: 99%